ATENCIÓN AL CLIENTE POR PARTE DE LOS EMPLEADOS DE LA COOP. DE AHORRO Y CRÉDITO 13 DE ABRIL - Chipantiza Figueroa, Gabriela Estefania (2018)
the Cooperativa de Ahorro y Crédito "13 de Abril was founded on August 30 1966 by a group of teachers with great dreams and hopes, with purpose that the payment of their salaries improves since at that time delayed up to 3 months and in this way to be able to satisfy the common needs of each one of them.